2010
DOI: 10.1007/s11046-010-9302-9
|View full text |Cite
|
Sign up to set email alerts
|

Adherence Patterns of Histoplasma capsulatum Yeasts to Bat Tissue Sections

Abstract: The adherence of Histoplasma capsulatum yeasts to lung, spleen, liver, gut, and trachea cryosections of Artibeus hirsutus bats and inbred BALB/c mice (control) was studied after in vitro yeast-tissue incubations. Candida albicans yeasts were used as a well-known adherent fungal model in the mice host, and latex beads were used as a negative adherence control. Adhered yeast cells were identified by using crystal violet staining and the immunoperoxidase method with specific antibodies. H. capsulatum yeasts adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The demonstration that H. capsulatum yeasts can adhere to different organ cryosections also provides evidence of an important mechanism for yeast colonization and dissemination that involves yeast cell adherence to host tissue architecture, probably including cellular surfaces and extracellular components (Sua´rez-Alvarez et al 2010). …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The demonstration that H. capsulatum yeasts can adhere to different organ cryosections also provides evidence of an important mechanism for yeast colonization and dissemination that involves yeast cell adherence to host tissue architecture, probably including cellular surfaces and extracellular components (Sua´rez-Alvarez et al 2010). …”
Section: Discussionmentioning
confidence: 94%
“…So, the spectrophotometric method and the XTT reduction assay used in this study made it possible to evaluate fungal biofilm growth accurately. The characteristics of some surface molecules of a parasite could be important in parasite-adherence patterns and in the selection of the route of internalization into the host cells, as well as in extracellular dissemination (Sua´rez-Alvarez et al 2010). According to Long et al (2003) alveolar macrophages are able to recognize unopsonized H. capsulatum yeasts and microconidia during a infection via the b-chain (CD18) family of adhesion-promoting glycoproteins, LFA-1 (CD11a/CD18), CR3 (CD11b/CD18), and CR4 (CD11c/CD18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[204][205][206][207][208][209][210][211][212][213][214][215][216][217]. Important virulence factors for these fungi include thermal dimorphism which allows the pathogen to adapt/survive inside the host, and the capacity to produce biofilm in vitro, expression of phospholipase and melanin production [218][219][220][221][222][223].…”
Section: Paracoccidioidomycosismentioning
confidence: 99%
“…It is one such respiratory fungal infection that accounts for about half a million cases per year only in the US. 108 The ability of H. capsulatum to form biofilms remained unknown for a long time until identified by Suárez-Alvarez et al 109 The researchers showed that H. capsulatum yeasts could adhere to the cryosections of different organs and further provided evidence for an important mechanism of colonization and spread of the yeasts, which involves adhesion of the microorganisms to the host tissues, including the cell surface and extracellular components. Two years later, Pitangui et al 110 demonstrated the in vitro ability of H. capsulatum to form biofilms and evaluated its invasion potential in cell lines.…”
mentioning
confidence: 99%